First Insights Into the Horizontal Movements of Whale Sharks (Rhincodon typus) in the Northern Arabian Sea - Arrowsmith, Lucy M.; Paidi, Charan Kumar; Bloch, Farukhkha Husenkha; John, Sajan; Choudhury, Binod Chandra; Kaul, Rahul; Sequeira, Ana M. M.; Pattiaratchi, Charitha B.; Meekan, Mark G. (Frontiers in Marine Science, 2021)
Whale sharks off the western coast of India have suffered high levels of fishing pressure in the past, and today continue to be caught in small-scale fisheries as by-catch. Additionally, coastlines in this region host very large and growing human populations that are undergoing rapid development. This exacerbates ongoing anthropogenic threats to this species such as pollution, habitat loss, and ship traffic. For these reasons, there is an urgent need for data on movement patterns of whale sharks in this region of the Indian Ocean. Here, we address this issue by providing the first data on the horizontal movements of whale sharks tagged in the northern Arabian Sea off the western coast of the Indian state of Gujarat. From 2011 to 2017, eight individuals, ranging from 5.4 to 8 m were tagged and monitored using satellite telemetry. Tag retention varied from 1 to 137 days, with the sharks traveling distances of 34 – ∼2,230 km. Six of the eight individuals remained close to their tagging locations, although two sharks displayed wide ranging movements into the Arabian Sea, following frontal zones between water masses of different sea surface temperatures. We explore the relationship between the movement patterns of these whale sharks and the physical and biological processes of the region.